2021
DOI: 10.1021/acs.jafc.0c05937
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phytochemical Compounds in Coffea arabica Whole Coffee Cherries and Their Extracts by LC-MS/MS

Abstract: The current work assessed the phytochemical contents of Arabica whole coffee cherry (WCC) and its two commercially available extracts: a minimum 40% chlorogenic acid (CGA; WCCE-1) and 70% caffeine (WCCE-2). Mass spectrometry analyses tentatively identified 219 phytochemicals in the three coffee samples, which is, so far, the largest number of identifications in a single study. A new group of CGA derivative namely caffeoylvaleroylquinic acid (CVQA) was identified in the three samples. Moreover, three 5-hydroxyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Our previous reports and studies from other laboratories have shown that coffee cherries are a rich source of polyphenolic compounds [ 13 , 14 , 15 , 16 ]. Various extraction and analytical methods have been used to identify several phenolic compounds, including phenolic acids, flavonoids, alkaloids, and organic acids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous reports and studies from other laboratories have shown that coffee cherries are a rich source of polyphenolic compounds [ 13 , 14 , 15 , 16 ]. Various extraction and analytical methods have been used to identify several phenolic compounds, including phenolic acids, flavonoids, alkaloids, and organic acids.…”
Section: Resultsmentioning
confidence: 99%
“…WCCE1 and WCCE2 were prepared from whole coffee cherries and were commercially marketed as Coffeeberry ® by VDF FutureCeuticals, Inc. (Momence, IL, USA). WCCE1, commercially marketed as “Neurofactor™”, was produced using a proprietary multi-step 70% ethanol/water extraction and purification method, followed by spray-drying [ 13 ]. WCCE2, commercially marketed as “Coffeeberry ® Energy 70%”, was prepared by using a proprietary water extraction and purification procedure and was subsequently spray-dried [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the observed beneficial effects of WCCE in the extant literature that are commensurate with evidence from other polyphenol-rich materials [7,21,22] and in light of the mounting evidence suggesting that polyphenols have neurotrophic effects [23][24][25][26], it is important to consider the chemical properties of WCCE that may drive the mechanisms involved in such effects. Recently, the phytochemical profile of WCCE was determined by a high-resolution non-targeted mass spectrometry approach (Figure 1) [27]. Importantly, one of the most abundant and widely distributed polyphenols in plants are chlorogenic acids, which are well-known for their antioxidant, anti-inflammatory, antihypertensive, and therapeutic properties [28][29][30].…”
Section: Introductionmentioning
confidence: 99%